KANDUNGAN GIZI DAN MUTU PROTEIN TEPUNG BIJI KELOR TERFERMENTASI - Ni'mawati Sakinah; Endang Prangdimurti; Nurheni Sri Palupi (Jurnal Teknologi dan Industri Pangan, 2019)
Moringa oleifera seed has the potential as a source of new food ingredients having high nutritional content, especially protein. The objective of this study was to evaluate the effect of fermentation toward biochemical composition and in vitro protein digestibility (IVPD) of Moringa seed flour. Fermentation was carried out by soaking the seeds at room temperature (30±2°C) for 24 and 48 h, either naturally (without starter addition) and with starter addition (i.e. commercial starter containing lactic acid bacteria/LAB). Unfermented and fermented seeds were processed into flour and their proximate composition, antitrypsin, tannin and IVPD were analyzed. The statistical methods used were ANOVA and Duncan's test at confi-dence level of 95%. The best treated flour was chosen using the De Garmo method and the amino acid profile was then analyzed. Protein digestibility-corrected amino acids (PDCAAS) were calculated to deter-mine the biological quality of proteins. The results showed that fermentation affected the changes in bio-chemical composition of the flour. Longer fermentation time could reduce the crude protein and antitrypsin content in both types of fermentation. On the other hand, there was an increase in tannin content during fermentation. The IVPD also increased by 75% at 48 h fermentation from the initial digestibility of raw seeds of 71%, thus increase in tannin content did not affect the IVPD. Natural fermentation of moringa seeds for 48-hour resulted in the best flour with IVPD and PDCAAS values of 75.33% and 0.18 (18.31%) respectively.